Challenging the 4- to 5-minute Rule: From Perimortem Cesarean to Resuscitative Hysterotomy. Issue 4 (December 2016) - Rose, C.H.; Faksh, A.; Traynor, K.D.; Cabrera, D.; Arendt, K.W.; Brost, B.C.
Abstract : ( Am J Obstet Gynecol 2015;213(5):653–656. 653.e1) About 1/12, 500 deliveries are complicated by antepartum maternal cardiac arrest, causative factors of which include hemorrhage, amniotic fluid embolism, heart failure, sepsis, anesthetic complications, and trauma. The maternal survival rate ranges from 17% to 59% and fetal survival rates from 61% to 80%. This article is a review of current practices for maternal cardiopulmonary arrest (MCPA) management and also proposes a maternofetal management strategy that differs from the current 4 to 5 minute rule for perimortem cesarean delivery (PMCD).